2020
DOI: 10.1002/batt.202000088
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for In Situ Determination of the Active Surface Area Changes of Li–Ion Battery Electrodes

Abstract: Li‐ion batteries have been of a great interest for over three decades. A geometric electrode surface area is generally used for Li‐ion electrochemical parameters calculations. Since the real electrode is a complex system composed of the thick porous structure, the contact surface area between the active mass and electrolyte is far larger than geometrical. This approximation leads to a large deviation of obtained results, especially within different laboratories and for volume and surface changing materials, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The η increases slightly during each plateau, indicating a rising trend of R CT . During battery charging, the volume of graphite particles keeps increasing and ECSA increases consequently [23] . Meanwhile, the increase of R CT in the plateau mainly results from the enrichment of Li + on graphite surface.…”
Section: Resultsmentioning
confidence: 97%
“…The η increases slightly during each plateau, indicating a rising trend of R CT . During battery charging, the volume of graphite particles keeps increasing and ECSA increases consequently [23] . Meanwhile, the increase of R CT in the plateau mainly results from the enrichment of Li + on graphite surface.…”
Section: Resultsmentioning
confidence: 97%
“…Two semicircles ascribe to the SEI resistance and charge transfer resistance are overlapped with each in the Nyquist plots because of the similar time constants. [ 34 ] The smaller interfacial resistance of the SiO x @Li 0.75 PAA suggests the fast electrochemical kinetics of the SiO x @Li 0.75 PAA during cycling. The slopes obtained by the impedance ( Z ′) and reciprocal square root of frequency (ω −1/2 ) fitting were used to compare the Li–ion diffusion ability of different electrodes during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…The surface morphology of the Gr anode exhibits no Li plating at 1900.0 s (Figure 3g), corresponding to an NI of 111.5 %. Since an 8.5 % increase in the ESCA of Gr is revealed by Ratynski and coworkers, [23] it is conservative to set 110.0 % as the NI for onset Li plating. The growth of C S values after 2500.0 s exhibits a linear trend with a larger slope compared to the results at a lower C-rate (Figure S6), which is attributed to the dendritic morphology at 1.0 C. By comparing the variation trend of C S values in Figure 3e with that of DCM tests on saturated LiC 6 (Figure S7), it can be concluded that the Li + intercalation is absent in the total current flow after 2500.0 s (the insert images in Figure 3h and l).…”
Section: Resultsmentioning
confidence: 99%